The Rule for Offsetting Damages with Benefits in Determining the Compensation Under Article 200 of the Labour Code - Tsoneva, Silvia (Yearbook of the Law Department, 2022)
The study examines the applicability and demonstration of the general principle of offsetting damages with benefits (compensatio lucri cum damno) in determining the compensation due by the employer to the employee for damages arising from workplace accident or occupational disease. The nature of the social security compensation and pension are analysed alongside with the hypotheses of their deduction from the amount of pecuniary and/or non-pecuniary damages. The problem is examined in the context of the question posed in the interpretative case 1/2023 of the GACC of the Supreme Court of Cassation. Particular attention is given to the deduction of the sums paid under contracts made by the employer for compulsory insurance of employees for the risk of “workplace accident”. In addition, other cases that are relevant to the topic are discussed. In conclusion, an attempt is made to formulate a general conclusion on the rule of offsetting damages with benefits and the criteria for its applicability in determining the amount of compensation under Article 200 of the Labour Code.